Multi-longitude case studies comparing the interplanetary and equatorial ionospheric electric fields using an empirical model - Kelley, M.C.; Nicolls, M.J.; Anderson, D.; Anghel, A.; Chau, J.L.; Sekar, R.; Subbarao, K.S.V.; Bhattacharyya, A. (My University, 2007)
Electric fields have been determined at three longitudes corresponding to Peru, India, and the Philippines. We compare these fields to applying a frequency-dependent linear transfer function (TF) to the dawn-to-dusk component of the interplanetary electric field (IEF). The TF is based on four years of simultaneous observations of the IEF and equatorial data. The model gives good results for the prompt penetrating electric field (PPE) in the case of an oscillatory IEF with a period in the 1–2 h range, when the interplanetary magnetic field remains southward for a long period and, to a lesser extent, when the IEF can be described as a square wave. There is evidence that a disturbance dynamo (DD) effect contributes on the dayside, where it leads to suppression of the normal quiet time pattern. A very strong counter-electrojet was seen at two locations during a time of persistent Bz south and was not predicted by the model or a linear scaling of the IEF. This suggests that suppression (and even reversal) of the E -region dynamo can occur in a large storm. Both the data and the model yielded a long-lived response to a sustained southward interplanetary magnetic field. Previously suggested By effects on equatorial electric fields are confirmed by a sequence of three distinct spikes in the By component of the IMF, one of which had no associated Bz change and yet was reproduced by two independent ground magnetometer-based electric field determinations. The sometimes remarkable agreement of a linear relationship between the equatorial and interplanetary electric fields shown here and elsewhere remains somewhat mysterious for such an apparently complex system.
Keywords: Middle atmosphere; Interplanetary electric field (IEF); Equatorial ionosphere; Atmosphere interactions; Turbulence; Electric fields; Empirical model